MENIMBANG RELASI GENDER DALAM KELUARGA [Sebuah Tela’ah Kritis-Filosofis-Humanistik] - Rohinah, Rohinah (IAIN Pekalongan, 2012)
Abstract : The discourse of gender equality as promoted by the feminist movement is intended to criticize the practice of the tradition in which men dominate women in various lines of life, including family life and more specifically is in relation to the child. Such patriarchialism gains legitimacy from many directions, including from the customary laws, traditions, and theological-philosophical. Apart from the discursive conflict, both sides that are opposite each other have the same attitude in treating their child to build a discourse concerning their rights to the child. In this condition, the child is as passive party, where he is just a dead object and has no contribution during the determination of the rights of parents over their children. Criticism also comes with a reverse way of thinking, which puts the child in an active position, the object of life, and contributes. The rights of fathers and mothers that have established and understood differently as in patriarchialism and feminism then reformulated. This reformulation leads to a new discourse that could be called a post-feminism. Abstrak : Wacana kesetaraan gender seperti yang dipromosikan oleh gerakan feminis dimaksudkan untuk mengkritik praktek tradisi di mana laki-laki mendominasi perempuan dalam berbagai lini kehidupan , termasuk kehidupan keluarga dan lebih khusus dalam kaitannya dengan anak . Seperti keuntungan patriarchialism legitimasi dari berbagai arah , termasuk dari hukum adat , tradisi , dan teologis - filosofis . Terlepas dari konflik diskursif , kedua belah pihak yang saling berlawanan memiliki sikap yang sama dalam mengobati anak mereka untuk membangun wacana tentang hak-hak mereka untuk anak . Dalam kondisi ini , anak sebagai pihak yang pasif , di mana ia hanya benda mati dan tidak memiliki kontribusi dalam penentuan hak-hak orang tua atas anak-anak mereka . Kritik juga datang dengan cara kebalikan dari berpikir , yang menempatkan anak dalam posisi aktif , objek hidup , dan memberikan kontribusi . Hak-hak ayah dan ibu yang telah ditetapkan dan dipahami secara berbeda seperti di patriarchialism dan feminisme kemudian dirumuskan . Reformulasi ini mengarah ke wacana baru yang bisa disebut post - feminisme.